SESSION "CLASSICAL PHILOLOGY, BYZANTINE AND MODERN GREEK PHILOLOGY OF THE COUNCIL ON PHILOLOGY EMA (Moscow, January 15-17, 2014) - Елена Леонидовна Григорьян (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2014)
Grigoriyan E.L.